Promenade Among Words and Things The Gallery as Catalogue, the Catalogue as Gallery - Lending, Mari 1969- (2015)
In the mid nineteenth century new casting techniques allowed for the production of huge architectural fragments. Well-selected collections could ideally display perfect series in galleries in which the visitor could wander among monuments and experience architecture history on full scale. The disembodied material of plaster was considered capable of embodying a number of modern historical taxonomies and aesthetical programs, most importantly chronology, comparison, style, and evolution. Veritable showcases of historicism, the casts could illustrate in spatial arrangements new conceptions on the history, contemporaneity and future of architecture. Plaster cast became a main medium in which to publish antiquities as novelties for grand audiences, taking the printed and published beyond the two-dimensional space of words and images. However, due to the increasing market of casts and their sheere size and weight, the reproductions as mounted in the galleries often behaved as unruly as architecture does outside curatorial control. In the end only the catalogues, the paper versions of these imaginary museums were capable to create the orders that their plaster referents constantly aspired to destroy. An important chapter in the history of the architecture museum these plaster monuments belong to a part of architectural print culture in which catalogues were curated and galleries edited. Metaphors drawn from the realm of writing saturated the discourse on the display of casts. Images and texts fluctuated and the image-objects were compared to books, paper, pages, documents and libraries but above all to illustrations inviting promenades in time and space.
Keywords: Plaster casts, monuments, catalogues, images, circulation, 19th century